2003
DOI: 10.1038/sj.ejcn.1601601
|View full text |Cite
|
Sign up to set email alerts
|

Copper and zinc intake and serum levels in patients with juvenile rheumatoid arthritis

Abstract: Objective: To evaluate the copper and zinc intake and serum levels in patients with juvenile rheumatoid arthritis (JRA), considering the pauci and polyarticular types, the disease activity and duration, the number of inflamed joints and the use of corticosteroids therapy. Design: Cross-sectional study with control group. Setting: Outpatients of the pediatric rheumatology public health clinic, of the Universidade Federal de São Paulo=Escola Paulista de Medicina, Brazil. Subjects: Forty-one patients with JRA wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Recently, Ala et al [4] reported that plasma copper levels of patients with RA did not change in comparison with healthy controls although zinc levels were decreased. Amancio et al [5] reported that serum copper, but not zinc, was decreased in juvenile RA. Tuncer et al [8] reported a rise in erythrocyte zinc and plasma copper levels and a decrease in erythrocyte copper and plasma zinc levels in patients with RA relative to controls.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, Ala et al [4] reported that plasma copper levels of patients with RA did not change in comparison with healthy controls although zinc levels were decreased. Amancio et al [5] reported that serum copper, but not zinc, was decreased in juvenile RA. Tuncer et al [8] reported a rise in erythrocyte zinc and plasma copper levels and a decrease in erythrocyte copper and plasma zinc levels in patients with RA relative to controls.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a few studies investigated the possible role of zinc, copper, and selenium in the etiology and pathogenesis of RA [2][3][4][5], but the results are conflicting so further studies are needed on the subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12, 2010 An adequate intake of copper during chronic inflammatory diseases, such as rheumatoid arthritis, may influence the efficiency of the organic serum response. 5 Sorenson [6][7][8] attributed the anti-inflammatory activity to the action of the complexes in vivo due to their inherent physico-chemical properties, but Rainsford et al 9 have suggested that the activity may be due to a counter-irritant mechanism triggered by free copper ions. A number of researchers have found that some complexes show similar but not significantly greater anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…1). Blood levels of copper are increased in several pathological conditions, such as Wilson disease, Indian childhood cirrhosis, juvenile rheumatoid arthritis, thalassemia, and sickle cell anemia (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%